Atherosclerosis Is Associated with Neutrophil Lymphocyte Ratio As An Inflammatory Marker in Type 2 Diabetes Mellitus Patients with Coronary Artery Disease - Bhuiyan, Mohammad Monzurul Alam; Sultana, Tuhin; Islam, Md Saiful; Borua, Dhiman; Ahmed, Mostaque; Khan, Sarwar Hossain; Paul, Debatosh; Rahman, Quddusur; Pandit, Harimohan; Ahmed, AN Nashimuddin (Journal of Dhaka Medical College, 2016)
Background: Increased neutrophil lymphocyte ratio is associated with major adverse outcomes of cardiac events in type 2 diabetes mellitus (DM) patients. Objective: To assess the NLR as an inflammatory marker in atherosclerosis in type 2 DM patients with coronary artery disease (CAD). Methods: This case control study was conducted in the Department of Clinical Pathology in collaboration with Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2014 to February 2015. Total 134 patients were enrolled in this study who were waiting for coronary angiography in the Department of Cardiology, BSMMU; 84 cases were considered as Group I (DM with CAD) and 50 controls were Group II (DM without CAD). A 2 ml of blood was collected in EDTA tube from the patients prior to coronary angiogram for complete blood count (CBC) were measured by haematology autoanalyzer, rechecked manually and NLR was calculated in the Department of Clinical Pathology, BSMMU. Coronary artery disease with 50% coronary artery stenosis and more critical lesion that were diagnosed by coronary angiography were included in this study as cases. Coronary artery disease with less than 50% coronary artery stenosis that was diagnosed by coronary angiography was included in this study as control. Results: NLR was higher in CAD positive group compared to group without CAD negative in type 2 DM patients (2.76 (±0.74) vs. 1.56 (±0.15), p<0.001). Conclusion: With the help of neutrophil lymphocyte ratio we can take preventive measure and precaution to reduce the progression of atherosclerosis in type 2 diabetic patients with coronary artery disease. J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 24-29